Tackling health inequalities in a public health organization: the case of the Barcelona Public Health Agency - Gloria Pérez; M. Isabel Pasarín; Vanessa Puig-Barrachina; Katherine Pérez; Maica Rodríguez-Sanz; Lucia Artazcoz; Carme Borrell (BMC, 2022)
Abstract Background Municipalities are important actors in the implementation of policies to tackle health inequalities, which requires political will, the availability of financial support, and technical and human resources. With the aim of aligning with local government political priorities, in 2017 the Barcelona Public Health Agency (Agència de Salut Pública de Barcelona, henceforth ASPB), which is responsible for the public health functions of the city, launched a strategy to improve the approach to tackling health inequalities in all its services. The objectives of this study were to show how social health inequalities were addressed in the ASPB from 2017 to 19 and to describe which actions were proposed after a participatory process aiming to create a plan to systematically incorporate health inequalities in ASPB actions. Methods The ASPB has 304 workers, 8 directors and 20 services or departments. Participatory methodologies were carried out: 1) semi-structured interviews with department heads (N = 12, 60%); 2) world cafe workshops open to a group of workers (N = 63, 37%); 3) a Quick and Colorful voting session open to a group of workers (N = 108, 63%); and 4) Hanlon matrix with 19 actions to be prioritized (N = 12 services, 60%). Results Semi-structured interviews and world cafe workshops provided 40 potential actions. After a step by step process of participatory prioritization, seven lines of action emerged: 1) to make progress in collaborative networking; 2) to promote policy evaluation; 3) to increase the ability of the ASPB to evaluate policies to reduce health inequalities; 4) to incorporate the axes of inequalities in all ASPB products; 5) to improve information on vulnerable groups; 6) to incorporate the gender perspective; and 7) to participate in an internal training plan to address health inequalities. Conclusions The participation of ASPB public health professionals and staff allowed the organization to design a shared plan of actions to address health inequalities. This experience could be useful for other municipalities whose political agendas include tackling inequalities in health.